2022
DOI: 10.1088/1361-648x/ac8403
|View full text |Cite
|
Sign up to set email alerts
|

A very low frequency (VLF) antenna based on clamped bending-mode structure magnetoelectric laminates

Abstract: As the development of wireless communication devices tends to be highly integrated, the miniaturization of very low frequency (VLF) antenna units has always been an unresolved issue. Here, a novel VLF mechanical communication antenna using magnetoelectric (ME) laminates with bending-mode structure is realized. ME laminates combines magnetostrictive Metglas amorphous ribbons and piezoelectric PMN–PT single crystal plates. From the simulation, we confirmed that the ME laminates can reduce the resonance peak fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…As mentioned earlier, researchers are particularly interested in achieving high α ME values at low frequencies to meet the requirements of detecting low-frequency weak magnetic fields. In this study, the results are compared with other reported low-frequency ME laminated composites prepared by partial bonding method, as illustrated in Figure . Through the implementation of vacuum packaging during the curing process, we successfully increased the value of α ME while simultaneously reducing the resonance frequency. This dual achievement holds significant benefits for the practical application of ME composite films, which have great advantages in low-frequency flexible devices.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, researchers are particularly interested in achieving high α ME values at low frequencies to meet the requirements of detecting low-frequency weak magnetic fields. In this study, the results are compared with other reported low-frequency ME laminated composites prepared by partial bonding method, as illustrated in Figure . Through the implementation of vacuum packaging during the curing process, we successfully increased the value of α ME while simultaneously reducing the resonance frequency. This dual achievement holds significant benefits for the practical application of ME composite films, which have great advantages in low-frequency flexible devices.…”
Section: Resultsmentioning
confidence: 99%
“…This is because we consider relatively simple ME structures with the same length and width as the magnetostrictive and piezoelectric phases in modeling. Other authors use more complex ME structures in their experiments, in which the lengths or widths of the magnetostrictive and piezoelectric phases do not coincide [ 34 , 35 , 40 , 48 , 49 , 50 ], and other additional layers are present in the design; for example, a permanent magnet [ 51 ]. Such complex constructions of ME composites require separate, rather laborious calculations for comparison with our theory when observing the CME effect.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the designed asymmetrical structure, which resulted in the ME antenna having resonance points corresponding to both a bent vibration mode and a length vibration mode. The resonance frequency associated with the bent vibration mode was lower than the resonance frequency of the length vibration mode [ 2 ]. In previous studies, the resonance frequency was found to strongly depend on the size effect of the ME composite [ 7 ].…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…In recent years, the very-low-frequency (VLF, 3–30 kHz) communication field has witnessed significant development, primarily driven by the growing demand for efficient and reliable communication systems [ 1 , 2 , 3 , 4 ]. This progress is particularly crucial in the field of geological exploration, where challenging environments such as long distances, underwater environments, underground environments and complex geological terrains make VLF communication increasingly important [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%